CdSe QD Biosynthesis in Yeast Using Tryptone-Enriched Media and Their Conjugation with a Peptide Hecate for Bacterial Detection and Killing - Sur, Vishma Pratap; Kominkova, Marketa; Buchtova, Zaneta; Dolezelikova, Kristyna; Zitka, Ondrej; Moulick, Amitava (Nanomaterials (Basel, Switzerland), 2019)
The physical and chemical synthesis methods of quantum dots (QDs) are generally unfavorable for biological applications. To overcome this limitation, the development of a novel "green" route to produce highly-fluorescent CdSe QDs constitutes a promising substitute approach. In the present work, CdSe QDs were biosynthesized in yeast Saccharomyces cerevisiae using a novel method, where we showed for the first time that the concentration of tryptone highly affects the synthesis process. The optimum concentration of tryptone was found to be 25 g/L for the highest yield. Different methods were used to optimize the QD extraction from yeast, and the best method was found to be by denaturation at 80 °C along with an ultrasound needle. Multiple physical characterizations including transmission electron microscopy (TEM), dynamic light scattering (DLS), energy-dispersive X-ray spectroscopy (EDX), and spectrophotometry confirmed the optical features size and shape distribution of the QDs. We showed that the novel conjugate of the CdSe QDs and a cell-penetrating peptide (hecate) can detect bacterial cells very efficiently under a fluorescent microscope. The conjugate also showed strong antibacterial activity against vancomycin-resistant Staphylococcus aureus (VRSA), methicillin-resistant Staphylococcus aureus (MRSA), and Escherichia coli, which may help us to cope with the problem of rising antibiotic resistance.
Keywords: biosynthesis; QDs; cell-penetrating peptide; tryptone; antibacterial